Drug-induced steatohepatitis. (1st February 2017) - Dash, Ajit; Figler, Robert A.; Sanyal, Arun J.; Wamhoff, Brian R.
ABSTRACT: Introduction : Drug induced steatohepatitis (DISH), a form of drug induced liver injury (DILI) is characterized by intracellular accumulation of lipids in hepatocytes and subsequent inflammatory events, in some ways similar to the pathology seen with other metabolic, viral and genetic causes of non alcoholic fatty liver disease and steatohepatitis (NAFLD and NASH). Areas covered : This paper provides a comprehensive review of the main underlying mechanisms by which various drugs cause DISH, and outlines existing preclinical tools to predict it and study underlying pathways involved. The translational hurdles of these models are discussed, with the example of an organotypic liver system designed to address them. Finally, we describe the clinical assessment and management of DISH. Expert Opinion : The complexity of the interconnected mechanistic pathways underlying DISH makes it important that preclinical evaluation of drugs is done in a physiologically and metabolically relevant context. Advanced organotypic tissue models, coupled with translational functional biomarkers and next-generational pan-omic measurements, may offer the best shot at gathering mechanistic knowledge and potential of a drug causing steatohepatitis. Ultimately this information could also help predict, detect or guide the development of specific treatments for DISH, which is an unmet need as of today.